Hydrogels in Simulated Microgravity: Thermodynamics at Play - Azadeh Sepahvandi; Joseph Johnson; Ava Arasan; Ryan Cataldo; Seyed Majid Ghoreishian (Gels)
Hydrogels have become indispensable in biomedical research and regenerative therapies due to their high water content, tissue-like mechanics, and tunable biochemical properties. However, their behavior under altered gravitational conditions—particularly simulated microgravity (SMG)—presents a frontier of challenges and opportunities that remain underexplored. This comprehensive review provides a detailed comparative analysis of hydrogel performance in normal gravity versus SMG environments, focusing on the structural, physicochemical, and thermodynamic parameters that govern their functionality. We critically examine how microgravity influences polymer network formation, fluid dynamics, swelling behavior, mechanical stability, and degradation kinetics. SMG disrupts convection, sedimentation, and phase separation, often leading to inhomogeneous crosslinking and altered diffusion profiles. These changes can compromise hydrogel uniformity, anisotropy, and responsiveness, which are essential for biomedical applications such as drug delivery, tissue regeneration, and biosensing. To address these limitations, we propose a thermodynamic framework that integrates osmotic pressure regulation, entropy-driven swelling, and pressure–temperature control to enhance hydrogel stability and functionality in low-gravity environments. The integration of predictive modeling approaches—including finite element simulations, phase-field models, and swelling kinetics—provides a robust pathway to design space-adapted hydrogel systems. The review also outlines future directions for optimizing hydrogel platforms in extraterrestrial settings, advocating for synergistic advances in material science, biophysics, and space health. These insights offer a strategic foundation for the rational development of next-generation hydrogel technologies tailored for long-duration space missions and planetary biomedical infrastructure.